​​Climate change adaptation and resilience for water management at Heathrow Airport - Coco, Andrew (Cranfield University, 2025)
​Increased duration and intensity of precipitation events are the most cited likely risk for the European aviation sector. Flooding events at airports cause disruptions to operations, increased labour and materials costs, and environmental degradation from stormwater runoff. Building climate resilience into airport infrastructure and operational models for future climate projections is paramount for climate proofing and adapting airports for future needs. A promising growing field of stormwater management practices known as Nature based solutions align with passive LID, low-impact development objectives while simultaneously providing multiple co-benefits (Social, Ecological, Economic) from their implementation. Through the examination of case studies, modelling studies, and lab based experimental studies I examined the scientific literature critically from the past 10 years. Airports provide a unique set of site characteristics and safety protocols that must be adhered to. The airport that was designed for this literature review case study was Heathrow Airport in the UK. Airside and landside general site NbS were identified with the assistance of aerial satellite imagery and SAR data showing the extent of notable historic flood events. Filter strips utilizing endophyte bonded grasses were the main choice for airside applications for their low maintenance requirements and low potential for bird strike safety concerns at the airport. Rainwater harvesting and green roofs were chosen for building areas depending on Heathrow’s decision to reclaim their rainwater harvesting infrastructure which is already in place.
Keywords: ​Nature-based Solutions; NbS; Low-impact development; Flood risk management; airports; SuDS